Direct and active participation of women in post-conflict reconciliation, reconstruction, and peace-building: needs, challenges and national and international obligations of sri lanka - Wijeyesekera, R. (University of Jaffna, 2012)
This paper analyses the social and legal issues concerning women’s participation in post-armed conflict and peace-building in Sri Lanka, and reiterates the necessity to include a gender perspective into the process relating to peace and security, and attempt to establish that a difference in nation-building is possible if the rhetoric about including women is translated into reality. Women have not been equitably represented in the official negotiations during cease-fire periods or in post-war peace process in the country, and as a result, issues and concerns particularly relating to women, have not been adequately addressed. The inclusion of women in peace-building may be justified on two broad grounds. (i) State obligation under the national Constitution, CEDAW, and the pledges made by states under the UN Security Council Resolution 1325 and 1889 to ensure the full, equal and effective participation of women at all stages of peace process, particularly in post-conflict reconstruction, planning and peace-building; (ii) on the basis of justice and equity to more than half the population of the country, considering their multiple-victimization during the conflict as well as afterwards, as IDPs, returnees and civilians who make an effort to rebuild their lives as widows and heads of households, and on the ground of women’s efficiency in peace-making. Despite all these reasons, and in spite of the abolition of more obvious discriminations from the law, women continue to be under-represented in the post-conflict reconciliation process. While the reasons for their non-inclusion vary, this paper analyses the impact of patriarchal structures and biases in the society on the gender-discriminatory application of the law and implementation of human rights of women that prevent women’s effective contribution in post-war reconstruction efforts. The analysis is based on constitutional and international obligations on the part of the government to include women in post-war peace process so as to ensure the enjoyment of civil and political as well as economic and cultural rights on a basis of equality.
Keywords: Post-war reconciliation; Women